Molecular imaging of fibroblast activity after myocardial infarction using a 68Ga-labeled fibroblast activation protein inhibitor, FAPI-04 - Varasteh, Zohreh; Mohanta, Sarajo; Robu, Stephanie; Braeuer, Miriam; Li, Yuanfang; Omidvari, Negar; Topping, Geoffrey; Sun, Ting; Nekolla, Stephan G.; Richter, Antonia; Weber, Christian; Habenicht, Andreas; et al. (Journal of nuclear medicine, 2019)
Heart failure remains a major source of late morbidity and mortality after myocardial infarction (MI). The temporospatial presence of activated fibroblasts in the injured myocardium predicts the quality of cardiac remodeling after MI. Therefore, monitoring of activated fibroblasts is of great interest for studying cardiac remodeling after MI. Fibroblast activation protein (FAP) expression is upregulated in activated fibroblasts. This study investigated the feasibility of imaging activated fibroblasts with a new 68Ga-labeled FAP inhibitor (68Ga-FAPI-04) for PET imaging of fibroblast activation in a preclinical model of MI. Methods: MI and sham-operated rats were scanned with 68Ga-FAPI-04 PET/CT (1, 3, 6, 14, 23, and 30 d after MI) and with 18F-FDG (3 d after MI). Dynamic 68Ga-FAPI-04 PET and blocking studies were performed on MI rats 7 d after coronary ligation. After in vivo scans, the animals were euthanized and their hearts harvested for ex vivo analyses. Cryosections were prepared for autoradiography, hematoxylin and eosin (H&E), and immunofluorescence staining. Results: 68Ga-FAPI-04 uptake in the injured myocardium peaked on day 6 after coronary ligation. The tracer accumulated intensely in the MI territory, as identified by decreased 18F-FDG uptake and confirmed by PET/MR and H&E staining. Autoradiography and H&E staining of cross-sections revealed that 68Ga-FAPI-04 accumulated mainly at the border zone of the infarcted myocardium. In contrast, there was only minimal uptake in the infarct of the blocked rats, comparable to the uptake in the remote noninfarcted myocardium (PET image-derived ratio of infarct uptake to remote uptake: 6 ± 2). Immunofluorescence staining confirmed the presence of FAP-positive myofibroblasts in the injured myocardium. Morphometric analysis of the whole-heart sections demonstrated 3- and 8-fold higher FAP-positive fibroblast density in the border zone than in the infarct center and remote area, respectively. Conclusion: 68Ga-FAPI-04 represents a promising radiotracer for in vivo imaging of post-MI fibroblast activation. Noninvasive imaging of activated fibroblasts may have significant diagnostic and prognostic value, which could aid clinical management of patients after MI.
Gesehen am 17.01.2019
Im Titel ist "68" in 68Ga-labeled hochgestellt